PSEUDOXANTHOMA ELASTICUM - Leite, Inês (2016)
Pseudoxanthoma elasticum (PXE) is a rare connective tissue disorder characterized by the progressive calcification and fragmentation of the elastic fibres of the skin, the Bruch´s membrane of the retina and the cardiovascular system. We report a case of an eight year old boy presenting with typical cutaneous manifestations and early ocular findings – peau d´orange pigmentation of the retina´s posterior pole.